The effects of drama-based activities towards rural students' affective involvement in speaking / Adelin Hamdan - Hamdan, Adelin (Faculty of Education, 2014)
This study investigated the effects of drama-based activities towards rural students' affective involvement in speaking. The module of the drama-based activities used was adapted from 'MAVERICKS' module which was introduced by the 'EtHOS Society' of the Faculty of Education, UiTM Shah Alam. The sample of this study involved 60 students from SMK Sijangkang Jaya which is a rural secondary school in Kuala Langat. The study employed a mix method system of gathering data using both Quantitative and Qualitative method. Questionnaire, representing the Quantitative method was given to the students before and after undergoing the 4 hour module. The Qualitative method was consisted of the facilitators' feedback and researcher's observation. The findings in this study indicated that drama-based activities give positive affective involvements towards rural students in speaking the target language which is English. The analysis also indicated that drama-based activities provide a non-threatening and authentic environment for students to practice speaking in English. These findings suggest that in order for students to gain courage in speaking the language, teachers need to put extra effort by becoming creative in integrating drama-based activities in their language teaching. Parents also play the role of expanding the language learning experience outside the classroom which is at home.